Crowns of "forgotten" standards in hardwood floodplain forests - Šálek, Lubomír; Machar, Ivo; Sivacioğlu, Ahmet; Zahradník, Daniel; Simon, Jaroslav; Jeřábková, Lucie (Czech Academy of Agricultural Sciences, 2017)
Floodplain forests have traditionally been managed using the coppice-with-standards silvicultural system for centuries. After abandoning this silvicultural system approximately in the 1950s the crown of standards (mature-aged trees) developed gradually under the growing influence of their tree competitors. This study examines the crowns of remnant oak and ash standards in a hardwood floodplain forest along the Morava River in the Czech Republic. 100 oak (Quercus robur Linnaeus) standards and 100 ash (Fraxinus excelsior Linnaeus) standards were randomly selected and the basic mensuration data as well as some ecological data, such as number of large dead branches, cavities, and height of the lowest large dead and green branches, were measured. The four nearest neighbour competitors were identified for each standard, and their height, distance and azimuth were measured. The DBH of the analysed oak standards ranged between 71 and 148 cm, and the projected oak crown area ranged between 125 and 533 m2. The ash DBH ranged between 71 and 127 cm, and projected ash crowns between 194 and 620 m2. To assess competitive pressure, we calculated an index as a ratio of the tangents of angles of regular and compressed crowns. Distance of competing trees was more important than their height in the ash data set, but not in the oak data set.
Keywords: reserved trees; oak; crown projection; ash; Forestry; crown competition; SD1-669.5; biodiversity; 15. Life on land